Use of digital techniques in the diagnosis of oral diseases in children - Katarzyna Cieślińska; Katarzyna Zaborowicz; Barbara Biedziak (Studia Medyczne, 2022)
Innovative computer techniques including artificial intelligence technique have been widely used in many areas, including dentistry. Increasing requirements in the field of diagnostics and dental treatment are conducive to the digitization of many areas of dentistry. The mentioned diagnosis and treatment are based on the knowledge of a specialist. The introduction of artificial neural networks (ANN) makes it possible to support the doctor’s decision regarding the diagnosis and treatment plan. The article presents the possibilities offered by artificial intelligence in the field of paediatric dentistry, both in terms of diagnostics and in the treatment process. There are many publications and ongoing research on the use of machine learning methods for dental treatment. Various types of analysis are based on digital images such as intraoral photographs, panoramic images, computed tomography images, and cephalometric radiography.